Coastal upwelling modulates winds and air-sea fluxes, impacting offshore wind energy - Pareja-Roman, L. Fernando; Miles, Travis; Glenn, Scott (Frontiers in Energy Research, 2024)
Coastal upwelling, marked by cool sea surface temperatures, modulates the wind stress and heat fluxes at the air-sea interface. However, the impact of upwelling on offshore wind power has been scarcely studied. This study uses satellite sea surface temperature data and a numerical model to examine how coastal upwelling shapes the diurnal evolution of the marine boundary layer, focusing on implications for offshore wind energy. The study region is the U.S. Mid Atlantic Bight, specifically the coast of New Jersey, known for its persistent summertime upwelling events. We run numerical experiments with upwelling, and upwelling artificially removed, to assess differences in the atmospheric response. For the wind event considered, results agree with theory where a stable, upwelling-cooled atmospheric boundary layer leads to reduced air-sea drag and turbulence intensity, higher wind speeds at hub height, and greater vertical shear relative to the scenario with upwelling removed. This response is likely caused by a sea breeze superimposed on onshore background winds. Experiments with parameterized turbines show that an 18-hour power generation at a lease area close to the shore was 6.5% higher with upwelling (4.86 GWh and 4.56 GWh, respectively). While upwelling can modulate offshore wind, the nature of the modulation is strongly dependent on the boundary layer regimes, background wind direction, and synoptic or mesoscale weather patterns.